How deep is your emotion? Emojis facial expressions on the emotional processing of text messages - Soares, Ana Paula (2021)
Despite emojis are already an integral part of human communication, little is known about how their use may affect the emotional processing of the text messages sent in platforms such as WhatsApp or Twitter. Here, we aimed to analyze how the brief presentation (34 ms) of emojis congruent with the emotional content of sentences designed to represent the five basic emotions, and neutral situations, relative to their verbal equivalents or the absence of any stimulus as control, affects the processing of the emotional content of these sentences using an affective appraisal task combined with the masked priming paradigm. Results showed that, although the use of emojis did not appear to affect the level of arousal elicited by the sentences, they did impact the speed with which these responses were made, though only in sentences associated with the emotions of sadness and disgust. Specifically, in these sentences, the prior presentation of the emoji produced longer responses when compared to the control stimulus. These results suggest that the use of emojis does not seem to offer advantages in the emotional processing of written messages, at least at early stages of processing.